2015
DOI: 10.3402/meo.v20.28654
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical medical student experience in a pediatric pulmonary clinic

Abstract: ObjectiveOur objective was to evaluate the educational value of introducing pre-clinical medical students to pediatric patients and their families in a subspecialty clinic setting.MethodsFirst- and second-year medical students at the University of Michigan seeking clinical experience outside of the classroom attended an outpatient pediatric pulmonary clinic. Evaluation of the experience consisted of pre- and post-clinic student surveys and post-clinic parent surveys with statements employing a four-point Liker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The network teaching resources is getting richer, in recent years. Not only there are abundant and flexible learning materials such as MOOC launched by various teaching platforms, but also professional rain classroom teaching software, DingDing, Tencent conference and other software are applied to field teaching and network teaching [17].…”
Section: Make Full Use Of Network Teaching Resources In Comprehensive...mentioning
confidence: 99%
“…The network teaching resources is getting richer, in recent years. Not only there are abundant and flexible learning materials such as MOOC launched by various teaching platforms, but also professional rain classroom teaching software, DingDing, Tencent conference and other software are applied to field teaching and network teaching [17].…”
Section: Make Full Use Of Network Teaching Resources In Comprehensive...mentioning
confidence: 99%
“…[7][8][9] In addition to increasing preparedness for clinical clerkships and residency, early integration of clinical experiences helps students develop patient-centered perspectives on healthcare, gain appreciation of multidisciplinary care, expand awareness of societal needs in medicine, and better prepare to address healthcare inequities. [10][11][12][13][14] This displacement has resulted in an increasing emphasis on clinical experience via telehealth and telephone-based outreach programs, which can provide students with an avenue for patient interaction and clinical exposure, as well as simultaneous opportunity to develop valuable new skills in remote patient care. 15 With its growing role in modern healthcare delivery, telehealth has become increasingly important; organizations such as the American Medical Association now advocate for the inclusion of telehealth as a core competency in medical education.…”
Section: Introductionmentioning
confidence: 99%
“…The initial years of medical education play an important role in shaping the attitudes of medical students towards medicine and training them for their future role as a physician [ 1 , 2 ]. The Carnegie Foundation for the Advancement of Teaching report [ 3 , 4 ] emphasized the need to integrate formal knowledge with clinical experience in the learning environment. Numerous studies have shown the benefits of exposing students to patients prior to traditional clerkship rotations [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%